The Transformation of Preaching Through the Evolution of Islamic Comics: From Traditional Narratives to the Influence of the Korean Wave in Digital Media - Lubis, Nikmah; Lakum, Lakum; Irwanto, Irwanto (Intiqad: Jurnal Agama dan Pendidikan Islam, 2025)
This study aims to analyze the adaptation of Islamic comics to technological advancements and contemporary cultural dynamics, with particular emphasis on their function as a medium of da’wah. The research applies a qualitative-descriptive approach with data collection conducted through netnography. The findings indicate a substantial transformation in both narrative structures and visual styles, accompanied by the growing use of digital platforms such as webtoons. Furthermore, Islamic comic creators have successfully incorporated elements of global popular culture, especially the Korean Wave, to attract younger audiences and expand the dissemination of religious messages. In conclusion, this study highlights that Islamic comics not only serve as creative instruments of da’wah but also operate as cultural bridges, enabling Islamic values to be conveyed in ways that are engaging, accessible, and contextually relevant to the younger generation.